When performativity fails: Implications for Critical Management Studies - Fleming, Peter; Banerjee, Subhabrata Bobby (Human relations (New York), 2016)
This article argues that recent calls in this journal and elsewhere for Critical Management Studies scholars to embrace rather than reject performativity presents an overly optimistic view of (a) the power of language to achieve emancipatory organizational change and (b) the capability of lone Critical Management Studies researchers to resignify management discourses. We introduce the notion of failed performatives to extend this argument and discuss its implications for critical inquiry. If Critical Management Studies seeks to make a practical difference in business and society, and realize its ideals of emancipation, we suggest alternative methods of impact must be explored.